2021
DOI: 10.1007/s10620-021-07231-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Adherence to a Gluten-Free Diet and Quality of Life of Celiac Patients After Transition to an Adult Referral Center

Abstract: Background Modalities for the transition to adult care of celiac patients diagnosed during childhood/adolescence and their impact on long-term adherence to a gluten-free diet (GFD-A), quality of life (QOL) and maintenance of follow-up in adulthood are unknown. Aims To evaluate whether timing of transition affects long-term GFD-A, QOL, and continuity of follow-up in adulthood and to identify predictors of long-term GFD-A. Methods Clinical and demographic data about pediatric care and adult follow-up at our cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Therefore, it would seem logical to support patients at that specific point, although more data is needed about the best practices for the transition process ( 52 ). In line with our earlier studies ( 15 , 28 ), presence of adulthood follow-up or membership of a celiac society were not associated with dietary adherence here, whereas in some other countries both of these have been reported to have a positive effect ( 19 , 53 ). External support could play a greater role if the general circumstances for a strict gluten-free diet are challenging.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, it would seem logical to support patients at that specific point, although more data is needed about the best practices for the transition process ( 52 ). In line with our earlier studies ( 15 , 28 ), presence of adulthood follow-up or membership of a celiac society were not associated with dietary adherence here, whereas in some other countries both of these have been reported to have a positive effect ( 19 , 53 ). External support could play a greater role if the general circumstances for a strict gluten-free diet are challenging.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, most patients reported occasional lapses and only 4% reported non-restricted gluten consumption or weekly lapses. So far a few studies with follow-up in adulthood of originally pediatric patients have reported variation in dietary adherence between 36–81% ( 12 , 18 – 20 ), whereas those diagnosed in adulthood have shown slightly better long-term figures of 40–98% ( 19 , 26 29 ). However, comparison between studies is not straightforward given the wide variation in study designs and characteristics of study populations, as well as in methods of measuring dietary adherence ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, Sciepatti et al recently reported that persistent symptoms despite good self-reported dietary adherence affected 38% of originally paediatric patients at their first adult consultation. 7 On a short-term gluten-free diet, symptoms have been reported in 34% of paediatric 6 and in 36%–52% of adult patients with coeliac disease. 5 6 Although these figures overlap, Sansotta et al reported symptom resolution to be better in children than in adults.…”
Section: Discussionmentioning
confidence: 99%
“… 5 6 Although these figures overlap, Sansotta et al reported symptom resolution to be better in children than in adults. 6 Most earlier studies have focused solely on gastrointestinal symptoms 5 10 24 or have not described the nature of symptoms in detail, 7 whereas Sansotta et al described the improvement of various extra-intestinal complaints to be poorer than gastrointestinal symptoms in both children and adults. 6 Taken together, our patients diagnosed in childhood reported fewer persistent symptoms on a strict diet in adulthood compared with the previously published figures.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest the authors to calculate the positive and negative likelihood ratios (LR), since they are not influenced by prevalence of the disease. Third, it is essential to consider both accuracy and precision of diagnostic research (3)(4)(5)(6)…”
Section: Tga-iga Titers In Children Withmentioning
confidence: 99%